An Efficient Approach to Access 2, 2‐Diarylanilines via Visible‐Light‐Promoted Decarboxylative Cross‐Coupling Reactions. Issue 9 (4th August 2021) - Luo, Cong; Zhou, Tongyao; Wang, Wei; Han, Pan; Jing, Linhai
Abstract: A straightforward protocol for the visible‐light‐promoted decarboxylative 1, 6‐conjugate addition of N ‐aryl glycines to para ‐quinone methides under transition‐metal‐free conditions is disclosed. This method provides scalable and efficient access to 2, 2‐diarylanilines with biological and pharmacologic potential in good to excellent yields (39 examples, up to 97% yield). The synthetic utility of this work has been illustrated in the efficient synthesis of 3‐substituted indoline. Abstract : An efficient method for the preparation of 2, 2‐diarylanilines was established through visible‐light‐promoted radical cross‐coupling of para ‐quinone methides ( p ‐QMs) with readily available N ‐aryl glycines. This simple reaction system features transition‐metal‐free conditions, high efficiency, mild conditions, and good functional group tolerance.